Student’s Difficulties In Writing An Essay Descriptive - Nazry Nasyifa; Aisyah Hafizha; Husnul Azizi Fauziah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to see, review, or find the difficulties of students while working on descriptive essays. The method used is a mixed method with indirect and direct interview methods summarized in the Google form. This research prepared as many as 5 questions related to obstacles and difficulties in working on descriptive essays so that students can provide their statements or answers about it. The number of students who participated in this study was 30 students. The results of the statements submitted by students are very diverse and also almost have similar factors about finding difficulties while working on descriptive essays.